2013
DOI: 10.1111/medu.12220
|View full text |Cite
|
Sign up to set email alerts
|

Tools for the direct observation and assessment of psychomotor skills in medical trainees: a systematic review

Abstract: Context The Accreditation Council for Graduate Medical Education (ACGME) Milestone Project mandates programmes to assess the attainment of training outcomes, including the psychomotor (surgical or procedural) skills of medical trainees. The objectives of this study were to determine which tools exist to directly assess psychomotor skills in medical trainees on live patients and to identify the data indicating their psychometric and edumetric properties. Methods An electronic search was conducted for papers pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 70 publications
(448 reference statements)
1
38
0
3
Order By: Relevance
“…In contrast, a considerably greater number of assessments are available for use in medical education: McKinley et al (2008) included 85 different scales in their review of assessments used in medical education. Our findings were similar to those of Jelovsek et al (2013), who found that there was limited reporting of measurement properties. Bould et al (2009) suggested that procedure unspecific assessments tended to miss errors in safety issues.…”
Section: Agreements and Disagreements With Other Studies Or Reviewssupporting
confidence: 81%
See 2 more Smart Citations
“…In contrast, a considerably greater number of assessments are available for use in medical education: McKinley et al (2008) included 85 different scales in their review of assessments used in medical education. Our findings were similar to those of Jelovsek et al (2013), who found that there was limited reporting of measurement properties. Bould et al (2009) suggested that procedure unspecific assessments tended to miss errors in safety issues.…”
Section: Agreements and Disagreements With Other Studies Or Reviewssupporting
confidence: 81%
“…Four recent systematic reviews were identified that reported the assessment of procedural skills in health professions education (Bould, Crabtree, & Naik, 2009;Jelovsek et al, 2013;McKinley et al, 2008;Morris et al, 2012). In general, these reviews focussed on medical education and few assessments relevant for use by allied health professions were identified.…”
Section: Agreements and Disagreements With Other Studies Or Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…OSATS ratings in the operating room demonstrated consistent expert-novice discrimination, but other aspects of the validity argument were inconsistently evaluated. However, a more recent systematic review of assessment tools for direct observation of psychomotor skills in medical learners recommended the OSATS global rating scale be implemented as a core component of a training program's evaluation methods (Class 1 ACGME grade) (Jelovsek et al 2013). This recommendation was based on assessing the global rating scale validity, reliability and utility in 12 studies.…”
Section: Important Issues For the Osats Validity Argumentmentioning
confidence: 99%
“…While previous reviews on technical skills assessment have either focussed on an overview of all of these tools (Moorthy 2003;Cook et al 2013;van Hove et al 2010), or examined one specific technical skill such as laparoscopic surgery (Aggarwal et al 2004), none have provided an indepth examination of the validity evidence supporting the intended use of a specific tool, and in particular we found no reviews focused on the OSATS. As the OSATS is the most widely-used technical skills assessment tool for both simulation-based (Cook et al 2013), and non-simulation based (van Hove et al 2010) technical skills assessment, and as the OSATS global rating scale is recommended for the direct assessment of psychomotor skills in medical learners (Jelovsek et al 2013), we believe the time is ripe for an in-depth examination of the validity evidence underlying the intended use of this tool.…”
Section: Introductionmentioning
confidence: 99%